Analysis Of The Influence Of Monetary Variables On Economic Growth In Indonesia - Sintia Daulay, Nurfia; Sihombing, Anisa; Evi Cahyani, Utari (Fakultas Ekonomi dan Bisnis Islam, 2020)
The development of the Indonesian economy is influenced by government policies, especially policies in the fiscal and monetary sectors, namely those concerning government spending, both routine and development expenditures, the money supply and also tax policies. The type of data used in this research is secondary data in the form of quarterly time series data for the period 2015 to 2022. The data source is obtained from publications of official state institutions such as Bank Indonesia (BI) and the Central Bureau of Statistics (BPS). The independent variables in this study are variables related to monetary policy transmission, namely Interest Rates (IR), Exchange Rates (NT), Money Supply (JUB), and Inflation (INF). While the dependent variable is economic growth (GDP at market prices). The analytical method used in this study is the Vector Error Correction Model (VECM) method assisted by E-views 10. The results show that inflation, the exchange rate and the BI Rate have a positive and significant effect on economic growth, while the money supply has no significant effect on economic growth. The short-term results show that inflation and the exchange rate have a positive and significant effect on economic growth, while the money supply and the BI Rate have no significant effect on economic growth in Indonesia for the 2015-2022 period.